Lithuania under the Tsars and the German Occupation (1795–1918): Discrepancies in the History Textbooks from the Period between the Two World Wars - Safronovas, Vasilijus (History / Istorija, 2022)
Abstract. The public figures who proclaimed Lithuanian independence at the end of the First World War treated their move as a restoration of the state, thereby presenting modern Lithuania as a continuation of the Medieval grand duchy. Previous research has already discussed an important prerequisite to further strengthen that continuity: in the interwar period, historians contributed significantly to the understanding that the grand duchy continued to exist after the Union of Lublin, as part of the Commonwealth of the Two Nations. However, less is known about how the period between the third partition of the Commonwealth and the proclamation of the modern Lithuanian state was approached. This article analyses how history textbooks published before 1940 represented the milestones of national oppression and revival during that period. Based on an analysis of several dozen history textbooks, the article aims to show how their authors contributed to the homogenisation of attitudes towards the period 1795 to 1918 in Lithuanian history, and addresses the question of how those who had ‘lived through the history’ tried to present it to the younger generation.